Spirits of the dead : Roman funerary commemoration in Western Europe - Carroll, Maureen (Oxford studies in ancient documents., 2006)
"Spirits of the Dead examines the importance attached to preserving the memory of the dead in the Roman world, and explores the ways in which funerary inscriptions can be used to reconstruct Roman lives, however fragmentarily and imperfectly. It is the only study to examine epigraphic, historical, and archaeological evidence in order to gain insight into the way Romans used funerary texts to establish a dialogue with their own society. Maureen Carroll brings together a large body of material from many geographical areas, shedding light on provincial and regional variation in funerary commemoration and even on the differences between funerary traditions of neighbouring towns." "Readership: archaeologists, ancient historians, classicists."--Jacket